Corruption, asset recovery, and the protection of property in public international law : the human rights of bad guys - Ivory, Radha (Cambridge, United Kingdom : Cambridge University Press, 2014)
'In recovering assets that are or that represent the proceeds, objects, or instrumentalities of grand corruption, do states violate the human rights of politically exposed persons, their relatives, or their associates? Radha Ivory asks whether cooperative efforts to confiscate illicit wealth are compatible with rights to property in public international law. She explores the tensions between the goals of controlling high-level, high-value corruption and ensuring equal enjoyment of civil and political rights'--
Concepts, sources, and case studies -- Criminalizing corruption -- Cooperating for the purposes of confiscation -- Asset recovery and european human right(s) to property -- Asset recovery and other regional rights to property -- General conclusions.
Includes bibliographical references (pages 302-348) and index.
Keywords: International criminal law; Forfeiture; Reparation (Criminal justice); Right of property